Nikah Sirri dalam Tinjauan Fikih Munakahat dan Konteks Sosial Kontemporer - Azhari, Azhari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2025)
Nikah sirri is a form of marriage that is legally valid under Islamic jurisprudence (fiqh) but is not officially recorded by state institutions. This practice remains prevalent in Indonesian society due to various factors, including economic limitations, social pressures, and hidden polygamy. This study aims to analyze nikah sirri from the perspective of fiqh munakahat and to examine its implications in a contemporary social context. The research applies a library research method using a descriptive-analytical approach through the examination of classical and contemporary Islamic legal texts, along with sociological and legal literature. The findings indicate that while nikah sirri is religiously valid, the lack of legal documentation creates significant vulnerabilities for women and children. The study also reveals that such unregistered marriages often marginalize justice within family structures and contribute to legal uncertainty in modern governance systems. Therefore, a contextual reinterpretation of fiqh that prioritizes maqashid al-shari’ah is necessary for reforming Islamic family law. The main contribution of this research lies in offering an integrative approach that combines Islamic jurisprudence and socio-legal perspectives to develop more comprehensive and applicable solutions to the phenomenon of nikah sirri in Indonesia.